Apply AcryditeTM Gel Separation to Solve Time-Table Problem - Zhixiang Yin; Min Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Time-table problem is a classical NP-complete problem. Algorithm of DNA computing for time-table problem was obtained with introducing the technology of AcryditeTM gel separation. Each class period viewed as a graph vertex was mapped into DNA molecules chain. With the probe coding, the gel column was constructed to arrange the order of DNA chain through biological reaction. The problem was solved by gel column that performs the basic core processing and extraction that makes the result visible. The minimum number of cycles of arrangement was the minimum number of class hours. The simulation results show that the algorithm compared with others is very easy and feasible. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1271